(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This work aims to carry out an analytical study of a Libyan organization, analyzing its management system then comparing it with international standard ISO 9001:2000, showing the differences and setting-out improvements of work program taking into consideration the following:  Assessment of the existing system of the selected organization.  Finding-out the weak areas in the QMS of the selected organization.  Setting-out necessary procedures needed for the system improvement showing lack of manpower as well as work procedure.  Identify the difference ratio existing between the organization and the requirements of the international standard. This work is expected to enable and improve the selected organization and to qualify it in order to obtain the ISO 9001:2000 certification, presuming that the results and comments have been followed precisely.